Strategi Akselerasi Penanganan Rumah Tidak Layak Huni melalui Transformasi Intervensi Berbasis Data Tunggal Sosial Ekonomi Nasional (DTSEN) di Kabupaten Sikka - Maria Ernestin Sodin (Universitas Nusa Nipa Maumere, 2026)
The management of Uninhabitable Houses (Rumah Tidak Layak Huni/RTLH) in Sikka Regency faces a critical challenge due to the high number of inadequate housing units distributed across both urban and rural areas with complex geographical characteristics. The primary obstacle to effective policy implementation stems from the limited capacity of local government interventions in improving housing quality on a sustainable basis, which is largely caused by poor-quality housing data and the absence of an integrated single-data information system. This policy paper aims to formulate an acceleration strategy for addressing RTLH through the reform of data governance that is accurate, efficient, and accountable. Using Eugene Bardach’s (2012) policy analysis framework to evaluate alternative solutions based on technical feasibility, economic viability, political acceptability, and administrative operability, this study identifies the transformation of intervention mechanisms based on the National Integrated Socio-Economic Data (Data Tunggal Sosial Ekonomi Nasional/DTSEN) as the most appropriate policy option. To ensure long-term sustainability, the paper recommends a Phased Convergence Strategy, whereby data cleansing and matching processes based on DTSEN are implemented at the upstream level and subsequently integrated into the “One Data RTLH Sikka” digital platform in the medium term. This operational strategy is further strengthened through the enactment of a Regent Regulation (Peraturan Bupati) on Data Governance and the Mechanism for Determining Eligible Beneficiaries of Decent Housing Assistance, providing a legally binding framework for policy implementation. By positioning village and urban ward governments as the frontline actors in conducting by-name-by-address (BNBA) field verification, the policy minimizes the risks of inclusion and exclusion errors, eliminates budget overlaps, and optimizes local innovative programs such as the TERKASIH House Assistance Scheme (Terima Kunci Siap Huni – “Receiving the Key to a Ready-to-Occupy House”). The implementation of these recommendations is expected to promote data-driven governance that accelerates the reduction of extreme poverty and enhances the effectiveness of housing assistance programs in Sikka Regency.